2023
DOI: 10.1038/s41540-023-00284-7
|View full text |Cite
|
Sign up to set email alerts
|

Employing active learning in the optimization of culture medium for mammalian cells

Abstract: Medium optimization is a crucial step during cell culture for biopharmaceutics and regenerative medicine; however, this step remains challenging, as both media and cells are highly complex systems. Here, we addressed this issue by employing active learning. Specifically, we introduced machine learning to cell culture experiments to optimize culture medium. The cell line HeLa-S3 and the gradient-boosting decision tree algorithm were used to find optimized media as pilot studies. To acquire the training data, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…The present study first demonstrated ML-assisted medium specialization for differentiated bacterial growth. ML was remarkably significant in medium optimization for microbial and mammalian cells 21,26 , which could be widely applied to synthetic construction and production 43,44 . The present study provided alternative applications in medium development for selective culture.…”
Section: Discussionmentioning
confidence: 99%
“…The present study first demonstrated ML-assisted medium specialization for differentiated bacterial growth. ML was remarkably significant in medium optimization for microbial and mammalian cells 21,26 , which could be widely applied to synthetic construction and production 43,44 . The present study provided alternative applications in medium development for selective culture.…”
Section: Discussionmentioning
confidence: 99%
“…It predicts the growth fitness upon novel medium compositions made artificially and selects those in which the predicted growth fitness is significantly improved. Machine learning prediction for better activity has successfully improved the cellular activity of mammalian cells [ 99 ], the translation activity of bacteria or cell-free systems [ 100 , 101 ], and the activity of bacterial secondary metabolism [ 102 ]. The successful applications strongly suggest that machine learning-mediated methodologies can benefit genome reduction or minimisation.…”
Section: Machine Learning-based Minimal Genome Methodsmentioning
confidence: 99%
“…Repeated rounds of active learning improve the prediction accuracy of machine learning and the growth fitness in the finetuned medium. The availability and efficiency of active learning for medium optimization have been demonstrated in the case of the mammalian cell [ 99 ]. Active learning has also been utilized in drug discovery [ 105 ], structural biology [ 106 ], and translational activity in cell-free systems [ 101 ].…”
Section: Machine Learning-based Minimal Genome Methodsmentioning
confidence: 99%
“…Recently, synthetic biologists have begun to explore its application in various use cases; early examples include synthetic gene design [43], as well as automated optimisation of metabolic engineering tasks [44-47], media optimization in cell-free systems [48], an in silico design of genetic control circuits [49]. Various bespoke approaches have been developed for media optimisation in mammalian cell bioproduction [50-52], and recently several software packages have been developed for the optimisation of gene circuits and metabolic pathways [53]. Our work is a novel application of active learning in combination with metabolomic readouts and thus offers substantial opportunities for data- and cost-efficient optimisation of complex bioprocesses across scales.…”
Section: Introductionmentioning
confidence: 99%